Creative problem solving for managers - Proctor, Tony (Routledge, 1999)
Using case studies and case histories, together with extensive diagrams, examples and thought-provoking questions, this textbook provides the most up-to-date and extensive approach to creative problem solving.
Keywords: Problem solving.; Management.; Problem Solving; Résolution de problème.; Gestion.; management.; BUSINESS & ECONOMICS -- Decision-Making & Problem Solving.; Management; Problem solving